Comparing Perceived and Objective Measures of Bikeability on a University Campus: A Case Study. (June 2021) - Kellstedt, Debra K.; Spengler, John O.; Maddock, Jay E.
Using a participatory approach, this multi-method case study compared bicyclists' perceptions and physical indicators of bikeability on a college campus. Student focus groups discussed campus bikeability and mapped and graded common bicycle routes. Trained students conducted environmental audits with bicycle counts. In discussions, students expressed concerns about safe bicycle riding on campus, especially during peak times. Congestion with pedestrians, other bicyclists, and skateboarders created the potential for crashes. Five major routes were identified with map scores ranging from 21.4% to 70%. Audit scores ranged from 82.5% to 86.7%. Bicycle counts varied by time of day and ranged from 11 to 91 bicycles. Student perceptions of bikeability were poorer than objective assessments of routes. The audit tool did not differentiate enough between routes and did not capture conflict potential accurately. Specification is needed on audit tools to capture the potential for conflict between bicycling and other forms of active transport—especially in unique settings like college campuses. Campuses that have well-marked paths for pedestrians, bicyclists, and motor vehicles and that communicate the importance and ease of bicycling may see the most overall success when promoting active transport options.